1995
DOI: 10.1093/oxfordjournals.jbchem.a125001
|View full text |Cite
|
Sign up to set email alerts
|

Some Characteristics of the Fluorescence Lifetime of Reduced Pyridine Nucleotides in Isolated Mitochondria, Isolated Hepatocytes, and Perfused Rat Liver In Situ

Abstract: By extensively examining the experimental conditions for time-resolved spectrophotometry of non-transparent light scattering systems, we demonstrated the feasibility of quantitative analysis of both the fluorescence lifetime and intensity of reduced pyridine nucleotides in living tissues, suspensions of isolated liver mitochondria, and hepatocytes, as well as hemoglobin-free perfused rat liver being used systematically for measurements. The fluorescence decay was analyzed by the maximum likelihood method with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 0 publications
8
75
2
Order By: Relevance
“…However, changes in the free component have not been detected. Wakita et al (1995), in studies on rat liver mitochondria, report that the fluorescence signal is not due to changes in the environment (binding) but rather to changes in the amount of NAD(P)H. Kasimova et al (2006) find that the concentration of free NADH in isolated potato tuber mitochondria remains constant, regardless of the metabolic conditions or the total amount of NADH. When taken together, these considerations lead us to favor the idea that the troughs in the oscillatory signal represent an increase in NAD(P) 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, changes in the free component have not been detected. Wakita et al (1995), in studies on rat liver mitochondria, report that the fluorescence signal is not due to changes in the environment (binding) but rather to changes in the amount of NAD(P)H. Kasimova et al (2006) find that the concentration of free NADH in isolated potato tuber mitochondria remains constant, regardless of the metabolic conditions or the total amount of NADH. When taken together, these considerations lead us to favor the idea that the troughs in the oscillatory signal represent an increase in NAD(P) 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The troughs represent a decrease in NAD(P)H fluorescence, which could be due to two different processes. First, it could be due to a shift from bound to free NAD(P)H in which the bound form exhibits a much stronger fluorescence than that which is free (Wakita et al, 1995;Paul and Schneckenburger, 1996;Blinova et al, 2005). Second, it could be due to oxidation of NAD(P)H, where the oxidized form [NAD(P) 1 ] is nonfluorescent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fluorescence of NAD(P)H increases 8-to 12-fold when it is bound as a coenzyme (13,(18)(19)(20). From estimates in yeast cells, hepatocytes, and isolated mitochondria, it is accepted that most of the NAD(P)H of normal cells is bound in vivo (18,19,(21)(22)(23), which would lead to a Ï·10-fold overestimation of the NAD(P)H level. Thus, the unbound NADH standard curve does not rigorously apply here, but it can be used to determine an absolute upper limit for NAD(P)H changes.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of free/bound NADH varies significantly from 1.5:1 20 to 1:4. 21 For example, Wakita et al 23 were unable to detect free NADH in rat liver mitochondria regardless of their respiratory state, whereas Blinova et al 20 observed a high proportion of free NADH in pig heart mitochondria using a similar technique. Interestingly, Kasimova et al suggested that the free NADH concentration in plant mitochondria is kept constant under different metabolic conditions.…”
mentioning
confidence: 99%